2019
DOI: 10.1111/mve.12420
|View full text |Cite
|
Sign up to set email alerts
|

A single oral dose of fluralaner (Bravecto®) in dogs rapidly kills 100% of blood‐fed Phlebotomus perniciosus, a main visceral leishmaniasis vector, for at least 1 month after treatment

Abstract: Dogs are the reservoir host of zoonotic visceral leishmaniasis (VL) caused by Leishmania infantum (Kinetoplastida: Trypanosomatidae). Both subclinically-infected and sick animals can be infectious to competent phlebotomine vectors. The degree and duration of insecticidal efficacy of an oral dose of fluralaner (Bravecto ® ; Merck Animal Health) was determined in dogs exposed to bites of Phlebotomus perniciosus (Diptera: Psychodidae), a main Mediterranean vector of VL. Twelve dogs allocated to two groups of six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…longipalpis, with observed mortality of 100, 91.2, 48.7 and 37.5 on post-treatment days 1, 30, 60 and 90, respectively. Furthermore, a study with P. perniciosus showed that 96 h after blood meal, there was 100, 100 and 68.6% mortality on days 1, 28 and 84 post-fluralaner treatment, respectively [27]. In our study, 96 h after a blood meal, 100% mortality was recorded in Lu.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…longipalpis, with observed mortality of 100, 91.2, 48.7 and 37.5 on post-treatment days 1, 30, 60 and 90, respectively. Furthermore, a study with P. perniciosus showed that 96 h after blood meal, there was 100, 100 and 68.6% mortality on days 1, 28 and 84 post-fluralaner treatment, respectively [27]. In our study, 96 h after a blood meal, 100% mortality was recorded in Lu.…”
Section: Discussionsupporting
confidence: 54%
“…longipalpis 96 h after a blood meal. On the other hand, fluralaner efficacy against sand fly P. perniciosus was 100, 100 and 52.7 on days 1, 28 and 84 post-treatment, respectively [27]. The prolonged efficacy of fluralaner against Lu.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Fluralaner (Bravecto ® ) belongs to the isoxazoline compound class and acts as an antagonist of γ-aminobutyric acid (GABA)-gated chloride ion (Cl − ) channels, preventing the entrance of Cl − into the postsynaptic neuron, leading to hyperexcitability of the insect central nervous system [ 15 ]. Fluralaner (Bravecto ® ) has potent acaricidal activity against ticks and mites, as well as insecticide activity against infestations of phlebotomine sand flies, such as Phlebotomus papatasi [ 34 , 35 ], Phlebotomus perniciosus [ 36 ] and Lutzomyia longipalpis [ 37 ], in dogs, cats and poultry [ 38 42 ]. Dogs treated with fluralaner (Bravecto ® ) do not experience any side effects [ 43 ], and the compound has significant selectivity for insects over mammalian neurons [ 44 ].…”
Section: Introductionmentioning
confidence: 99%